1997
DOI: 10.1046/j.1365-2362.1997.1620711.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute saline infusion induces extracellular acidification and activation of the Na+/H+ exchanger in man

Abstract: The effect of acute expansion of the extracellular fluid volume (ECV) with isotonic (0.9%) saline on the activity of the lymphocyte Na+/H+ antiport (NHE) was studied in a total of 18 healthy volunteers. Saline was infused at a constant rate so that 4 mmol kg-1 b.w. was administered over 2 h. NHE activity was measured by quantifying cytosolic pH (pHi) recovery following acidification of the cells with propionic acid and by pH clamping at various pHi values between 7.2 and 5.8 using nigericin. Both methods demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
6
1
Order By: Relevance
“…However, with downregulated and potentially inhibited NHE1, one would expect a more severe intracellular acidosis in myocytes from ApoE Ϫ/Ϫ mice during simulated ischemia as NHE1 removes intracellular H ϩ in exchange for extracellular Na ϩ . Contrary to this expectation, acidosis was attenuated in this study, which may primarily be explained by the fact that the cells were superfused with an acidic Tyrode solution during hypoxic metabolic inhibition that provokes reverse-mode activity of the NHE1 just as during metabolic acidosis (21). Additional pH-regulating mechanisms transmitted via the Na ϩ /HCO 3 Ϫ symporter and the Cl Ϫ /HCO 3 Ϫ antiporter, although not studied here, could also have contributed to the pH changes we determined in the course of simulated ischemia.…”
Section: Discussioncontrasting
confidence: 73%
“…However, with downregulated and potentially inhibited NHE1, one would expect a more severe intracellular acidosis in myocytes from ApoE Ϫ/Ϫ mice during simulated ischemia as NHE1 removes intracellular H ϩ in exchange for extracellular Na ϩ . Contrary to this expectation, acidosis was attenuated in this study, which may primarily be explained by the fact that the cells were superfused with an acidic Tyrode solution during hypoxic metabolic inhibition that provokes reverse-mode activity of the NHE1 just as during metabolic acidosis (21). Additional pH-regulating mechanisms transmitted via the Na ϩ /HCO 3 Ϫ symporter and the Cl Ϫ /HCO 3 Ϫ antiporter, although not studied here, could also have contributed to the pH changes we determined in the course of simulated ischemia.…”
Section: Discussioncontrasting
confidence: 73%
“…But still other possible mechanisms may be involved, as previously mentioned (25). Enforced activity of cellular Na ϩ /H ϩ exchangers (18,36) as well as Na ϩ /H ϩ ion exchanges on the extracellular glycosaminoglycans (19) and/or a Na-induced expansion of extracellular volume, resulting in a decrease in HCO 3 Ϫ reabsorption (3,38,52,58), can contribute to mediation of the effect of NaCl on acid-base balance. Summarizing, with high NaCl intake, renal loss of bicarbonate but also excess acid production could be reasonably expected to affect acid-base status.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the reason for the decreased pH and bicarbonate concentration could not be an addition of metabolic acids by ingestion or infusion of acids, because the subjects' intake of acid‐inducing foods was not higher during high salt intake. Studies from Dusing et al ( (59)) and Kessler et al ( (60)) have shown significant stimulation of the Na + /H + exchanger during acute saline (0.9%) infusion accompanied by cytosolic alkalinization and extracellular acidification and accomplished by decreases in pH, bicarbonate, and base excess.…”
Section: Discussionmentioning
confidence: 99%